Relatório de estágio de ensino da prática pedagógica supervisionada - Saldanha, Ana; Jorge, José Reis (2015)
This stage report appears in connection to my master´s degree in pre-school and elementary school teaching, after being awarded my degree in Educação Básica, and it aims to present and analyze how practice and theory can work together in my future profession. The conclusions Iam about to present are possible due to my work in Casa Pia´s CED- centro de educação e desenvolvimento, with five year old students, in Planalto´s kindergarten´s four year old student´s and, finally, in Lumbar’s elementary EB1, nº 31, with second grade students. For the presentation of my practice I used two different dilemmas: for the kindergarten, I wanted to know how space organization of the classroom could or could not be a major factor in children´s learning improvement. Regarding the elementary school, it came to my attention if strategies for negotiated behaviors (what can and cannot be done within the classroom) with students, have a more positive outcome than in classes that do not follow this pre-established basics. Therefore, this report is expected to show, concerning the above questions, how will it be possible to conjugate both dilemmas, in both school levels, as I think they are inseparable for a good teacher´s practicing. Considering the kindergarten experience, I noticed that both schools have chosen to organize the class with specific and imaginary interest corners – cantinhos- of day life activities, such as little kitchens or beauty salons for girls or even mechanical workshops for boys. As for elementary school classes, it is definitely possible to affirm that the experimented strategies of controlling student´s behaviors had, in fact, a positive response on their behalf, even if for we, the adults/the teachers, the results appeared a little undervalued, as they were not fully achieved.